2012
DOI: 10.1186/1757-2215-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic alterations occur in ovarian tumor cells selected for combined resistance to carboplatin and docetaxel

Abstract: BackgroundCurrent protocols for the treatment of ovarian cancer include combination chemotherapy with a platinating agent and a taxane. However, many patients experience relapse of their cancer and the development of drug resistance is not uncommon, making successful second line therapy difficult to achieve. The objective of this study was to develop and characterize a cell line resistant to both carboplatin and docetaxel (dual drug resistant ovarian cell line) and to compare this cell line to cells resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 92 publications
(85 reference statements)
2
18
0
Order By: Relevance
“…Also, as neither UPN251-7C nor UPN251-7T had significant sensitivity to oxaliplatin while UPN251-6TALT did, this may indicate a novel mechanism of resistance being generated between this dual carboplatin/taxol resistant model and our singularly non-cross-resistant models. This evidence is supported by the finding of (Armstrong et al 2012) discussed above.…”
Section: Combined Resistance To Platinums and Taxanessupporting
confidence: 83%
See 1 more Smart Citation
“…Also, as neither UPN251-7C nor UPN251-7T had significant sensitivity to oxaliplatin while UPN251-6TALT did, this may indicate a novel mechanism of resistance being generated between this dual carboplatin/taxol resistant model and our singularly non-cross-resistant models. This evidence is supported by the finding of (Armstrong et al 2012) discussed above.…”
Section: Combined Resistance To Platinums and Taxanessupporting
confidence: 83%
“…Another study developed a dual carboplatin and docetaxel resistant subline from A2780 ovarian cancer cells which are cross resistant to both agents as well as two singularly resistant sublines resistant to each agent but not cross resistant to the other. All of the sublines were selected for in parallel (Armstrong et al 2012). Gene profiling revealed that the dual model contains genetic changes not present in the singularly resistant models demonstrating that combined drug resistance may not be a simple combination of changes present in singleagent resistant cell lines but can contain novel changes.…”
Section: Combined Resistance To Platinums and Taxanesmentioning
confidence: 99%
“…On the other hand, LGSC and MC is the least common among the major types of ovarian carcinomas. Therefore, we have used three different human ovarian cancer cell lines, A2780 (EC model) 47 , SKOV-3 (COC model) 48 , and CAOV-3 (HGSC model) 49 to check the in vitro anti-tumor activity of CeO 2 /DOX nanoparticles. The in vitro cytotoxicity and cell apoptosis experiments confirmed that CeO 2 /DOX exhibited higher tumour cell growth inhibition over free DOX in all of the tested human ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A major hurdle in HGSC management is the development of resistance to chemotherapy via both intrinsic and acquired mechanisms . In the current study, we investigated elements within the IFN pathway that potentially mediate the STAT1 associated pre‐existing tumour immune state and determine eventual response to chemotherapy via recruiting effector cytotoxic CD8 + T cells in the chemotherapy naïve HGSC tumours.…”
Section: Discussionmentioning
confidence: 99%